Development of a clinical decision rule for the early prediction of Shock-Refractory Out-of-Hospital cardiac arrest. (December 2022) - Lupton, Joshua R.; Jui, Jonathan; Neth, Matthew R.; Sahni, Ritu; Daya, Mohamud R.; Newgard, Craig D.
Abstract: Background: Nearly half of ventricular fibrillation or ventricular tachycardia (VF/VT) out-of-hospital cardiac arrest (OHCA) patients receive three or more shocks, often referred to as refractory VF/VT. Our objective was to derive a clinical decision rule (CDR) for the early stratification of patients into risk categories for refractory VF/VT. Methods: We included adults with non-traumatic OHCA in the Resuscitation Outcomes Consortium Epistry (2011–2015) with ≥ 1 EMS shock. We used Classification and Regression Tree analysis for CDR building using variables known at initial EMS rhythm analysis including age, sex, witness, location, bystander interventions, initial EMS rhythm, obvious non-cardiac etiology, and dispatch to arrival times. The outcome was refractory VF/VT (≥3 shocks). We calculated sensitivity, specificity, area under the receiver operating curve (AUROC), and odds ratios (OR). The rule was validated using the Portland Cardiac Arrest Epidemiologic Registry (2018–2020). Results: There were 17, 140 eligible patients and 8, 146 (47.5%) had refractory VF/VT. The optimal CDR (AUROC = 0.671) defined three groups: high-risk were any patients requiring an EMS shock after a bystander AED shock; moderate-risk were any non-EMS witnessed arrests with shockable initial EMS rhythms; and the remainder were low-risk. Refractory VF/VT increased across the low (30.7%), moderate (58.5%) and high-risk (84.8%) groups. Compared to low-risk, being moderate-risk or higher (OR [95% CI]:3.37 [3.16–3.59]; sensitivity 72.7%; specificity 55.9%) or high-risk (OR:12.63 [9.89–16.13]; sensitivity 5.4%; specificity 99.1%) had higher odds of refractory VF/VT. Results was similar in the validation cohort (n = 765, AUROC = 0.672). Conclusions: Patients at higher risk for refractory VF/VT can be identified early in EMS care.